2017
DOI: 10.1017/jns.2017.49
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a concise food list for use in a web-based 24-h dietary recall tool

Abstract: Foodbook24 is a self-administered web-based 24-h dietary recall tool developed to assess food and nutrient intakes of Irish adults. This paper describes the first step undertaken in developing Foodbook24 which was to limit participant burden by establishing a concise list of food items for inclusion in the tool. The aim of the present study was to evaluate whether using a concise food list (as opposed to an extensive list) with generic composition data would influence the estimates of nutrient intakes in a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…For myfood24-UK, an extensive database including generic and branded items (n = 40,274) was developed in an elaborate process [11]. For Foodbook24, a contrary approach was chosen by limiting the items in the underlying database to 751 generic food items [37]. The authors assumed that the limitation of food items limits participants' burden and observed only small differences in estimated nutrient intake when comparing this concise food list with an extensive one (n = 2319 items).…”
Section: Discussionmentioning
confidence: 99%
“…For myfood24-UK, an extensive database including generic and branded items (n = 40,274) was developed in an elaborate process [11]. For Foodbook24, a contrary approach was chosen by limiting the items in the underlying database to 751 generic food items [37]. The authors assumed that the limitation of food items limits participants' burden and observed only small differences in estimated nutrient intake when comparing this concise food list with an extensive one (n = 2319 items).…”
Section: Discussionmentioning
confidence: 99%
“…There were, however, nutrients that were not correlated such as the intakes of monounsaturated fat and intakes that were significantly different from the semi-weighed food diary, for example, protein and fiber. In an evaluation of the shortened food-list (n=751) for integration into Foodbook24 [ 20 ], it was observed that there was less agreement for mean daily intake of monounsaturated and saturated fat due to the changes in food composition data that resulted from merging similar food and drink items that had similar composition into single food or drink descriptors or codes. Expanding the number of food items within this category may improve the agreement between methods for these nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The food composition data linked to the NANS dataset are derived from UK food composition tables [ 18 ] and the Irish Food Composition Database (IFCDB) [ 19 ]. The reduction process of the list involved the merging of food codes of a similar description and/or composition [ 20 ]. The aim of the reduction process was to reduce the food list that participants would have to search through to describe their dietary intake, thus reducing participant burden without compromising the nutrient composition output.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concise food list integrated into the Foodbook24 tool was developed using nationally-representative food consumption data and food grouping structure from the National Adult Nutrition Survey (NANS) (2008–2010) [ 17 ]. Both the development of the tool itself and the establishment of the shortened food list for integration into the tool have been described elsewhere [ 18 , 19 ]. The NANS food composition database used data from McCance and Widdowson’s The Composition of Foods, sixth and fifth editions, plus all nine supplemental volumes to generate nutrient intake data.…”
Section: Methodsmentioning
confidence: 99%